Shockwave medicine - Wang, Ching-Jen 1939-; Schaden, Wolfgang; Ko, Jih-Yang 1955- (Translational research in biomedicine / series editor Samuel H.H. Chan, 2018)
This comprehensive reference work provides a detailed overview of shockwave therapy, a relatively new clinical specialty in modern medicine. It follows the evolution of Extracorporeal Shockwave Therapy (ESWT) from its initial stage as the gold standard for the disintegration of kidney stones to its regenerative effects in biological tissues. Starting with the basic principles of shockwave treatment, the book goes on to review its application in musculoskeletal disorders, including osteonecrosis of the hip, tendinopathy, fracture treatment, and treatment of sports related injuries. The application of ESWT in cardiovascular diseases is discussed. This includes preclinical and clinical applications for ischemic cardiovascular disease and effects on angiogenesis and anti-inflammation-molecular-cellular signaling pathways. The treatment of urinary diseases and erectile dysfunction by ESWT is elaborated. The book concludes with a discussion of future prospects of the shockwave therapy. Scholars and research fellows interested in shockwave medicine will benefit greatly from this work. It is also a useful clinical resource for nephrologists, urologists, cardiologists, and orthopedists.